Vertical eddy iron fluxes support primary production in the open Southern Ocean - Takaya Uchida (Nature Portfolio, 2020)
The Southern Ocean is an important sink of carbon via the biological pump. Here authors run high-resolution physical/biogeochemical simulations of an open-Southern Ocean ecosystem forced with a realistic seasonal cycle and confirm that (sub)mesoscale iron transport across the mixing-layer base sustains primary productivity.